Modelling emission trends from non-constant time series of PM10 concentrations in Christchurch, New Zealand. (17th November 2010) - Appelhans, Tim; Sturman, Andrew; Zawar-Reza, Peyman
This paper presents an attempt to model the trend of emissions through analysis of a time series of PPM10 concentrations in Christchurch, New Zealand. Emissions are not constant over time, but show high seasonality. Fluctuations are removed by creating a time series in which concentrations do not show dependency on ambient air temperature. Remaining meteorological influences are removed through multiple linear regression. Finally, a moving average filter is applied to reveal the low-frequency trend in the residuals of the meteorologically adjusted time series. The modelled trend shows a peak in emissions in 2001-2002 with a steady decrease thereafter.